Unraveling CoNiP-CoP2 3D-on-1D Hybrid Nanoarchitecture for Long-Lasting Electrochemical Hybrid Cells and Oxygen Evolution Reaction - Sekhar, S. Chandra; Ramulu, Bhimanaboina; Han, Man Ho; Arbaz, Shaik Junied; Nagaraju, Manchi; Oh, Hyung-Suk; Yu, Jae Su (Wiley-VCH Verlag, 2022)
Evolving cost-effective transition metal phosphides (TMPs) using general approaches for energy storage is pivotal but challenging. Besides, the absence of noble metals and high electrocatalytic activity of TMPs allow their applicability as catalysts in oxygen evolution reaction (OER). Herein, CoNiP-CoP2 (CNP-CP) composite is in situ deposited on carbon fabric by a one-step hydrothermal technique. The CNP-CP reveals hybrid nanoarchitecture (3D-on-1D HNA), i.e., cashew fruit-like nanostructures and nanocones. The CNP-CP HNA electrode delivers higher areal capacity (82.8 mu Ah cm(-2)) than the other electrodes. Furthermore, a hybrid cell assembled with CNP-CP HNA shows maximum energy and power densities of 31 mu Wh cm(-2) and 10.9 mW cm(-2), respectively. Exclusively, the hybrid cell demonstrates remarkable durability over 30 000 cycles. In situ/operando X-ray absorption near-edge structure analysis confirms the reversible changes in valency of Co and Ni elements in CNP-CP material during real-time electrochemical reactions. Besides, a quasi-solid-state device unveils its practicability by powering electronic components. Meanwhile, the CNP-CP HNA verifies its higher OER activity than the other catalysts by revealing lower overpotential (230 mV). Also, it exhibits relatively small Tafel slope (38 mV dec(-1)) and stable OER activity over 24 h. This preparation strategy may initiate the design of advanced TMP-based materials for multifunctional applications.